2010
DOI: 10.1002/mawe.201000585
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ti in hard metal alloys – Part I: structural and microstructural analysis

Abstract: Nanosized WC, and binders Co, Ti and Ti-Co, are used to process hardmetals. Titanium (Ti) was proposed to reduce and even replace the Co in these composites, verifying the effectiveness of the new binders. Samples of nanosized WC with 10 wt% Co, 9 wt% WC 1 wt% Ti -Co, WC-10 wt% Ti were cold compacted at 200 MPa and sintered at 1500 8C during 1 hour under vacuum of 10 -2 mbar for the processing of hardmetal were performed. The structural characterization by X-ray diffraction and microstructure by scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The fabricated composites obtained from mixtures containing 50 wt.% Cu and 30 wt.% Cu showed a Vickers hardness of 490 ± 50 HV1 and 715 ± 55 HV1, respectively. Lamim et al [18] revealed that WC-Ti sintered by SPS at 1500 • C for 1 h presents three phases (W 2 C, TiC, and (W 1−x Ti x )C), and interesting mechanical properties, such as hardness (1575 HV30) and fracture toughness (11.05 MPa.m 1/2 ). Similarly, Ouar et al [19] have investigated the magnetic and mechanical properties of Co 80 Ni 20 nanopowders prepared by using a polyol process and then being consolidated by using SPS at 500 and 600 • C for 5 min and under a pressure of 100 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated composites obtained from mixtures containing 50 wt.% Cu and 30 wt.% Cu showed a Vickers hardness of 490 ± 50 HV1 and 715 ± 55 HV1, respectively. Lamim et al [18] revealed that WC-Ti sintered by SPS at 1500 • C for 1 h presents three phases (W 2 C, TiC, and (W 1−x Ti x )C), and interesting mechanical properties, such as hardness (1575 HV30) and fracture toughness (11.05 MPa.m 1/2 ). Similarly, Ouar et al [19] have investigated the magnetic and mechanical properties of Co 80 Ni 20 nanopowders prepared by using a polyol process and then being consolidated by using SPS at 500 and 600 • C for 5 min and under a pressure of 100 MPa.…”
Section: Introductionmentioning
confidence: 99%